A study of interferometric distance measurement systems on a prototype rapid tunnel reference surveyor and the effects of reference network errors at the International Linear Collider - Dale, J; Dr John Dale (2009)
The International Linear Collider (ILC) aims to collide electrons and positrons with a centre of mass energy of 500GeV and a luminosity of 2×1034 cm−2 s−1. To achieve this luminosity, the nominal final emittance of the electron and positron beams have to be below 10μm.rad horizontally and 0.04μm.rad vertically. To prevent the emittance from becoming too large, the main linacs will require alignment at an unprecedented level. The ILC main linacs will be aligned with respect to a reference network which runs along the entire length of the tunnel. The Linear Collider Alignment and Survey (LiCAS) Rapid Tunnel Reference Surveyor (RTRS) is the prototype of a device proposed to survey the ILC reference network. The LiCAS RTRS has several measurement systems; its Frequency Scanning Interferometry (FSI) measurement system is studied in this thesis. The FSI system has three distinct sub-systems: the reference interferometers, the external FSI measurement system and the internal FSI measurement system. The errors on the length of the reference interferometers are shown to be of the order of 1.1μm (0.3ppm). The external FSI measurement system is shown to measure distances close to 0.42m with errors of ±1.9μm stat ±0.16μm syst and the internal FSI measurement system is shown to measure distances close to 4.2m with errors of ±0.24μm stat ±1.6μm syst. A survey of the ILC reference network using laser trackers is simulated without taking account of systematic measurement errors from refraction in the tunnel air. The simulated networks are used to misalign the simulated accelerators in Dispersion Matched Steering (DMS) simulations. The DMS simulations show that only 30% of the simulated accelerators produce an acceptable final corrected vertical emittance. It is further shown that the introduction of long range distance measurements between primary reference markers (PRMs) using GPS, reduces the long range error growth in the network, and that 95% of simulated accelerators give acceptable performance. A simplified network simulation model, which is capable of simulating reference networks surveyed by conventional and novel devices, is produced and compares favorably to full simulations.